Two-Sided Matching in the Audit Market - Li, Ken; McNichols, Maureen; Raghunandan, Aneesh (The Accounting Review, 2025)
ABSTRACT We develop and estimate a two-sided matching model of auditors and clients. We find evidence that auditors and clients engage in matching based on their preferences on both observable and unobservable characteristics. This matching appears to partly explain the “Big 4 effect” on audit outcomes: after controlling for the effects of matching, we find that the positive influence of having a Big 4 auditor on serious restatements and serious comment letter conversations with the SEC either weakens or disappears. Collectively, our results highlight the importance of accounting for two-sided matching between auditors and clients in understanding the influence of auditors on clients’ financial reporting practices. JEL Classifications: M40; M42